Agrochemicals on growth and hormonal relations of \'Micro-Tom\' and Arabidopsis roots under water deficit conditions - Santos, Valdinei Moreira dos (2016)
The increasing concerns launched by debates about climate changes added to the uncontrolled growth of world population have opened a market to natural inputs for a more sustainable agriculture. Taking those concerns together, it is very important to think in advance in terms of finding solutions to increase the food production, with improved quality and in a supposed changing environment. Natural substances such as seaweed biostimulants are coming up as inputs for crops yield and abiotic stress tolerance enhancement with increasing use in agriculture. In this scene, it is important to understand effects and mode of action of these substances on plant physiology to permit the development of consistent products and guarantee the delivery of solutions to growers that assist them in solving their needs. Therefore, this research was carried out aiming to understand the role of agrochemicals (classical plant growth regulators and seaweed biostimulants) on root development and hormonal relations of tomato \'Micro-Tom\' and Arabidopsis under water deficit conditions. Ascophyllum nodosum extracts (ANE) ability to stimulate endogenous hormonal responses in conditions of drought and osmotic stress was tested. We carried out experiments with two plant models: one is classically used in plant science studies and the other, a crop-like plant model whose scientific findings can be applied for several crops. We used tomato hormonal mutants and reporter lines grown in conditions of drought stress to study the effects of plant growth regulators and seaweed extracts on root growth and hormonal responses, respectively. Additionally, we tested in vitro the effects of these substances on root growth of Arabidopsis seedlings under osmotic stress conditions. The root development of tomato and Arabidopsis was negatively affected by the presence of water deficit caused by drought and osmotic stress, respectively. Gibberellins biosynthesis inhibitors only affected the root growth of gibberellin-deficient mutant (gib-3). Extracts of the same seaweed presented different effects on root growth of Arabidopsis seedlings and hormonal responsiveness in roots of tomato, possibly due to variability in their compositions. ANE A and B show opposite effects on root growth. ANE A promotes root growth, whereas ANE B shows inhibitory effects. These substances seem to have little influence on auxin responses in roots, however, they alter the balance between abscisic acid and ethylene under drought conditions. The standardization of the composition of seaweed extracts complemented with studies on their physiological and molecular effects in crops is crucial for the establishment of these agricultural inputs as one of the solutions for current and future requirements of food production.